Paeoniflorin improves psoriasis by modulating neutrophil extracellular traps in a mouse model of psoriasis - GUO Yunlong; SHI Wenli; ZHAO Rui; MO Jinxue; JIA Shuqing; LI Jingrong; WU Jiang; FANG Ruihua (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To investigate the effects of paeoniflorin on imiquimod-induced psoriasis in a mouse model and the underlying mechanisms. [Methods] Fifteen healthy BALB/C mice were randomly divided into the control, model, and model group-treated with low-, medium-, and high- doses of paeoniflorin, once daily for 7 days. The back skin of mice in the control and model groups were treated topically with Vaseline and imiquimod ointment, respectively. The imiquimod-treated mice were intragastrically given either saline or paeoniflorin at doses of 75 mg/(kg·d), 150 mg/(kg·d) and 300 mg/(kg·d), twice daily. The erythema and scaling on the treated area of the skin were observed. The skin biopsies were obtained from the treated area for H&E staining to observe the changes in histopathology and the skin thickness of the lesions, while immunofluorescence was applied to detect neutrophil infiltration. The expression levels of TNF-α and IL-17 mRNA were assessed with RT-PCR. In addition, Western blot was used to assess the expression of citrullinated histone 3 (CitH3). [Results] Compared with the model group, topical treatment with paeoniflorin attenuated multiple changes in the imiquimod-treated skin, including reduced erythema and scaling, decreased epidermal thickness and neutrophil infiltration, down-regulation of TNF-α and IL-17 mRNA expression (P<0.001 vs. imiquimod alone for all) in addition to reduction in expression levels of CitH3 (all P<0.05 vs. imiquimod alone). Moreover, paeoniflorin-induced changes in expression levels of IL-17 and CitH3 were dose-dependent (P<0.05 for both). [Conclusion] Paeoniflorin can modulate neutrophil extracellular traps, resulting in down-regulation of the expression levels of inflammatory cytokines, consequently alleviating cutaneous inflammation in a mouse model of psoriasis.